Plasma colloid osmotic pressure in healthy infants - Sussmane, Jeffrey B (BioMed Central, 2001)
BACKGROUND: The plasma colloid osmotic pressure (COP) plays a major role in transcapillary fluid balance. There is no information on plasma COP of healthy infants beyond the first post-natal week. The normal COP in healthy adult subjects (25 mmHg) is currently also applied as a reference value for healthy infants. This study was designed to test whether plasma COP values in healthy infants are the same as those in normal adults. METHODS: Plasma COP was measured in 37 male and female healthy infants from 1 to 11 months old. For this purpose, 1 ml blood was collected during the patient's regularly scheduled visit if the patient required any type of blood test for routine laboratory analyses. RESULTS: Plasma COP levels correlated slightly with increasing age from 1 to 9 months old (linear regression analysis; r(2) = 0.1, P < 0.049). We found no correlation between plasma COP and body weight at the same age (r(2) = 0.05, P = 0.155). The mean and standard deviation of COP in all infants was 25.1 ± 2.6 mmHg, which is almost identical to an average COP of 25 mmHg in healthy adult subjects. Arbitrary division of the infants into three different age groups (1–3 months [n = 11], 5–8 months [n = 13] and 9–11 months [n = 13]) showed an average increase of approximately 2 mmHg in COP of 9-month-old to 11-month-old infants, compared with 1-month-old to 3-month-old infants (one-way analysis of variance; P = 0.26). There was no gender difference in the COP level (unpaired t-test), with an average of 25.1 ± 2.4 mmHg in 19 male infants compared with 25.2 ± 2.9 in 18 female infants. The 95% confidence interval for COP in both male and female infants (n = 37) was between 24.3 to 26.0 mmHg, ranging from 19.5 to 30.3 mmHg, with a median value of 25.2 mmHg. CONCLUSIONS: The data accept the null hypothesis that the COP range in infants younger than 1 year old is similar to those observed in adult subjects. Our observations, compared with previously reported neonatal COP values, suggest that there is a sharp increase in COP within the first months after birth.